Bacterial enteric flora in children with acute enteritis compared to a healthy control group during summer - Bilir, Şule; Yuluğ, Nuran (The Turkish Journal of Pediatrics, 1973)
This study was carried out on 392 diarrheal and 111 control cases selected from those of the Hacettepe Out-Patient Pediatric Clinic between May and September 1972. The patients ranged in age from less than two weeks to 12 years. The rectal swab technique was employed.